Stakeholder Approach and Stakeholder Dialogue in 16 Hospital Markets in Western Europe - Del Corral, Jose Alberto (2010)
This individual work derives from the group report that gives account of the research and analysis of the generics drugs market of Austria, Belgium, Denmark, Finland, France, Germany, Greece, Ireland, Italy, Netherlands Norway, Portugal, Spain, Sweden, Switzerland and the United Kingdom.